Backstepping sliding mode control of electric linear load simulator. Issue 1 (February 2021) - Zhang, Jianwei; Fan, Yuanxun; Cao, Dawei; Lu, Pengcheng; Zhang, Jiacheng
Abstract: In order to solve the excess force problem in the electric linear load simulator (ELLS), a backstepping sliding mode controller based on the backstepping control idea is proposed. According to the function, the state of the system is divided into load torque subsystem and PMSM mechanical subsystem. First, the virtual control of the load torque subsystem is designed, and then the controller is designed for the PMSM mechanical subsystem, and the Lyapunov stability is proved. Finally, the simulation test is compared. The simulation results show that, compared with the traditional PID control, the controller based on the backstepping sliding mode design can effectively suppress the excess force and improve the loading accuracy of the system.